2021
DOI: 10.3389/ffgc.2021.695981
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Genetic Structure of the Insect-Vectored Conifer Pathogen Leptographium wageneri Suggests Long Distance Gene Flow Among Douglas-fir Plantations in Western Oregon

Abstract: Many fungi in the Ophiostomatales are vectored by bark beetles that introduce these fungi directly into their tree hosts. Most of these fungal associates have little effect on their hosts, but some can cause serious diseases. One such fungus, Leptographium wageneri, causes an economically and ecologically important tree disease known as black stain root disease (BSRD). For this study, 159 full genome sequences of L. wageneri were analyzed using a population genomics approach to investigate the epidemiology, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The present study is the first to demonstrate robust separation of the three L. wageneri varieties using multiple, non-rDNA loci. Although Bennett et al (2021) demonstrated strong separation between two varieties (L. wageneri var. wageneri and L. wageneri var.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study is the first to demonstrate robust separation of the three L. wageneri varieties using multiple, non-rDNA loci. Although Bennett et al (2021) demonstrated strong separation between two varieties (L. wageneri var. wageneri and L. wageneri var.…”
Section: Discussionmentioning
confidence: 99%
“…pseudotsugae isolates were identical to those within the genomic sequences of L. wageneri var. pseudotsugae isolates from Oregon used in the study of Bennett et al (2021). The clear phylogenetic separation warrants species designation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations